Biofilm Formation Behaviors on Graphene by E. coli and S. epidermidis. (25th October 2017) - Kanematsu, Hideyuki; Sato, M; Shindo, Kodai; Barry, Dana M.; Hirai, Nobumitsu; Ogawa, Akiko; Kogo, Takeshi; Utsumi, Yuichi; Yamaguchi, Akinobu; Ikegai, Hajime; Mizunoe, Yoshimitsu
Abstract : The formation of biofilm on graphene materials was investigated in this study. Two kinds of laboratory biofilm reactors were used to produce biofilms artificially on glass specimens (on the laboratory scale). One of them was a loop-type and the biofilms were measured by Raman spectroscopy. The other one was the static immersion test in a culture containing bacteria. The biofilm formation was evaluated by using crystal violet. We expected that the graphene would have a strong resistance against biofilm formation. However, on the contrary, graphene tended to become more sensitive to biofilm formation when the portion of graphene increased. When we come to think about the future application for graphene, it should not be used for biomaterials, but as sensor for infectious diseases.